Anglican Communion in Crisis : How Episcopal Dissidents and Their African Allies Are Reshaping Anglicanism - Hassett, Miranda Katherine (Book collections on Project MUSE., 2007)
The sign outside the conservative, white church in the small southern U.S. town announces that the church is part of the Episcopal Church--of Rwanda. In Anglican Communion in Crisis, Miranda Hassett tells the fascinating story of how a new alliance between conservative American Episcopalians and African Anglicans is transforming conflicts between American Episcopalians--especially over homosexuality--into global conflicts within the Anglican church. In the mid-1990s, conservative American Episcopalians and Anglican leaders from Africa and other parts of the Southern Hemisphere began to forge t.